2018
DOI: 10.1128/aem.02440-17
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate-Accumulating Bacteria: Potential Contributors to Mineral Dissolution in the Oral Cavity

Abstract: Bacteria that accumulate polyphosphates have previously been shown to dynamically influence the solubility of phosphatic minerals in marine settings and wastewater. Here, we show that dental plaque, saliva, and carious lesions all contain abundant polyphosphate-accumulating bacteria. Saturation state modeling results, informed by phosphate uptake experiments using the model organism Lactobacillus rhamnosus, which is known to inhabit advanced carious lesions, suggest that polyphosphate accumulation can lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…This decline in the microhardness could be attributed to the nature of the L. rhamnosus bacteria which is a phosphate accumulating bacteria that tends to accumulate polyphosphates resulting in the decline of phosphate in the surrounding which can lead to undersaturated conditions relative to the hydroxyapatite which might lead to demineralization potentials in dental plaque and lesser degrees of remineralization in the conducted study. 41 Though the inhibitory effect of group (A3) toothpaste containing probiotic against S. mutans growth was in accordance with many studies, 42 43 the remineralization capacity of this group needs prolonged studies in addition to in vivo studies to observe the actual effect of this toothpaste in oral conditions. Regarding the nGMP group (A4), the highest microhardness remineralization results were reported for this group.…”
Section: Discussionmentioning
confidence: 56%
“…This decline in the microhardness could be attributed to the nature of the L. rhamnosus bacteria which is a phosphate accumulating bacteria that tends to accumulate polyphosphates resulting in the decline of phosphate in the surrounding which can lead to undersaturated conditions relative to the hydroxyapatite which might lead to demineralization potentials in dental plaque and lesser degrees of remineralization in the conducted study. 41 Though the inhibitory effect of group (A3) toothpaste containing probiotic against S. mutans growth was in accordance with many studies, 42 43 the remineralization capacity of this group needs prolonged studies in addition to in vivo studies to observe the actual effect of this toothpaste in oral conditions. Regarding the nGMP group (A4), the highest microhardness remineralization results were reported for this group.…”
Section: Discussionmentioning
confidence: 56%
“…Owing to the relevance of lactobacilli in food and health, knowledge of the many poly-P functions in this microbial group will help to understand their physiology and interactions in bacterial communities and symbiotic relationships. These would cover positive but also negative aspects, as it has been recently described that poly-P accumulation in dental biofilm bacteria such as Lactobacillus rhamnosus may participate in teeth demineralization during carious lesion progression ( Breiland et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known, however, that polyphosphate kinases (ppk1 and ppk2) are primarily responsible for synthesizing and hydrolyzing polyphosphates in bacteria. These enzymes, and high polyphosphate storage capacity have been confirmed in pathogens such as P. aeruginosa (Zhang et al, 2002; Racki et al, 2017), but recent studies have shown that the Enterococcus genus has a low genetic potential for accumulating and hydrolyzing polyphosphate (Breiland et al, 2018). Therefore, a possible explanation of our findings is that E. faecalis , does not have the capacity to readily break down PPi to phosphate to make it more readily bioavailable.…”
Section: Resultsmentioning
confidence: 99%